Novos calcogenolatos de paládio(II) contendo núcleo [Pd2(-ER)2]: síntese e caracterização estrutural - Cechin, Camila Nunes (2016)
This work describes the synthesis and structural characterization of six new palladium(II) chalcogenolates derivatives containing [Pd2(-ER)2] core. These six compounds were characterized by single crystal X-ray diffraction and complementary methods as well. In order to get intermolecular Pd∙∙∙Pd interactions, it was planned the rational synthesis of these compounds by oxidative addition reactions of palladium(II) with organic dichalcogenides; and ligands substitution reactions. For this reason, it was explored the use of mercury chalcogenolates [Hg(ER)2] and organic dichalcogenides [(ER)2], where E = Se, Te and R = aryl, with palladium(II) halides and phosphine, bipyridine or phenanthroline ligands. The ligands substitution reactions using Hg{Te((2,6-OCH3)2C6H3)}2, palladium(II) halides and phosphine, bipyridine or phenanthroline ligands led to compounds 1, 3 and 4. The oxidative addition reaction of PdI2 by {Te((2,6-OCH3)2C6H3)}2, using PCy3, led to the formation of compound 2, and compounds 5 and 6 were formed by the ligands substitution reactions using Hg(SePh)2, palladium(II) halides and phosphine, bipyridine or phenanthroline ligands. It was observed that sterically hindered ligands avoided intermolecular Pd∙∙∙Pd interactions (compounds 1-4) while sterically unhindered ligands led to these contacts (compounds 5 and 6). The optical band gap of compounds 1-6 was calculated, in order to evaluate the optical properties and possible applications on the field of material science.